ANALISIS HUBUNGAN PENGGUNAAN PEMBAYARAN NON TUNAI, TINGKAT PENGANGGURAN, DAN INFLASI DI INDONESIA - Syamsiah, Thahira; Karimi, Syafruddin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
This study analyzes the impact of non-cash payment systems and the linkage between unemployment and inflation in Indonesia over the short run and long run. The transition from cash to non-cash transactions, driven by the Gerakan Nasional Non Tunai (GNNT) since 2014, requires an evaluation of its implications for economic stability. Based on monthly time series observations from January 2009 to August 2024, the variables examined include inflation as the dependent variable and the value of debit/ATM card transactions, credit card transactions, and the unemployment rate as independent variables. The analytical method employed is the Vector Error Correction Model (VECM). The findings reveal that in the short run, only credit card transactions have a positive and significant effect on inflation, while the other variables do not. Conversely, in the long run, all variables-debit/ATM card transactions, credit card transactions, electronic money, and the unemployment rate-exhibit a positive and significant impact. These results highlight that the digitalization of payment systems stimulates consumption and aggregate demand, thereby contributing to inflation dynamics, particularly in the long run. Accordingly, monetary and fiscal policies must be adjusted to safeguard price stability.